Sensing of biologically relevant d-metal ions using a Eu(iii)-cyclen based luminescent displacement assay in aqueous pH 7.4 buffered solution - GUNNLAUGSSON, THORFINNUR (My University, 2011)
1 Eu BPS was developed as a luminescent lanthanide sensor for use in displacement assays for detection of d-metal ions by monitoring the changes in the europium emission, which was quenched for iron(II), with a detection limit of B10 pM (0.002 lg L 1) for Fe(II) in buffered pH 7.4 solution.
PUBLISHED
Keywords: luminescent lanthanide sensor; d-metal ions; luminescent displacement; Nanoscience & Materials